We start with the following equality: -24 = -24 We write the number -24 in two different ways: 16 - 40 = 36 - 60 The numbers 16, 40, 36 and 60 can be written as follows: 4x4 - 2x4x5 = 6x6 - 2x6x5 We can add 25 on both sides of the equation without changing it: 4x4 - 2x4x5 + 5x5 = 6x6 - 2x6x5 + 5x5 Now we see that on both the left and the right side we have a squared binomial (the first squared term minus twice the product of the two terms plus the square of the second) (4 - 5) 2 = (6 - 5) 2 Eliminating the square on both sides of the equation gives: 4 - 5 = 6 - 5 Finally, by adding 5 on both sides, we get the result: 4 = 6 Obviously this demonstration has an error because we all know that 4 is not equal to 6 (or does anyone have any questions?